Answer:
<h2>48</h2>
Step-by-step explanation:
(1)
apple × apple × 2apple = 54
2apple³ = 54 <em>divide both sides by 2</em>
apple³ = 27 → apple = ∛27
apple = 3
(2)
apple + apple × green_apple = 24 <em>substituite apple = 3</em>
3 + 3 × green_apple = 24 <em>subtract 3 from both sides</em>
3 × green_apple = 21 <em>divide both sides by 3</em>
green_apple = 7
(3)
strawberry - bannana - banana = 0 → strawberry = 2banana
(4)
strawberry + banana + cherry = 24 <em>substitute from (3)</em>
2banana + banana + cherry = 24
3banana + cherry = 24
(5)
apple + banana - cherry = -1 <em>substitute apple = 3</em>
3 + banana - cherry = -1 <em>subtr3 from both sides</em>
banana - cherry = -4
Add both sides of (4) and (5)
3banana + cherry = 24
<u>+banana - cherry = -4 </u>
4banana = 20 <em>divide both sides by 4</em>
banana = 5
Substitute it to (4):
3(5) + cherry = 24
15 + cherry = 24 <em>subtract 15 from both sides</em>
cherry = 9
Substitute to the last equation:
3 + 5 × 9 = 3 + 45 = 48
/USED PEMDAS/
Answer:
A. 72
B. 3
C. 135
Step-by-step explanation:
A. 12 x 6 = 72
B. 15 x 3 = 45 so Nina raise 3x more money than Sandra
C. 45 x 3 = 135
Answer:
-2
Step-by-step explanation:
add the -5 and -11, then add on to it the 14
Hi there!
We are given the function -
and are told to find the limit of the function.
The limit would be n approaches infinity, giving us an answer of
-1.
Here is how you solve this:
Divide by (n + 1)! -
Now, we can refine the function -
Now, just simplify. This gives us -
We can use the rule
to simplify the whole thing to get 1. Finally, we plug it back into our second derived equation to get 1/-1, which simplifies to -1. Therefore, the answer is
-1. Hope this helped and have a great day!
Answer:
48 N
Step-by-step explanation:
The equation for force is
F = m * a
where F is force, m is mass, and a is acceleration
30N = m * 5m/s²
m = 6 kg
F = 6kg * 8m/s² = 48 N